What's the problem in problem gaming? - Enevold, Jessica (Sweden : Nordicom, 2018)
What's the problem in problem gaming? is a valuable contribution to the debates about young people's gaming habits and the highly contested concept of video game addiction. The chapters in the volume provide a number of perspectives on the issue, such as players' life conditions and lifestyle choices, problem gaming from a family perspective, the voices of treatment professionals, and how game design can become problematic. How problem gaming is framed is a highly relevant issue that affects policies surrounding the consumption of videogames. This anthology is a just in time contribution and an essential read for researchers in the field as well as for policymakers, social workers, clinical psychologists, teachers and others who encounter problem.
Includes bibliographical references.
Keywords: Video game addiction; Youth -- Social conditions; Video games -- Social aspects